2021
DOI: 10.3390/ani11010113
|View full text |Cite
|
Sign up to set email alerts
|

Herd-Level and Individual Differences in Fecal Lactobacilli Dynamics of Growing Pigs

Abstract: We studied the fecal lactobacilli count and species diversity of growing pigs along with immune parameters associated with intestinal lactobacilli. Thirty pigs categorized as small (S, n = 12) or large (L, n = 18) at birth were followed from birth to slaughter in two commercial herds, H1 and H2. Herds differed in terms of their general management. We determined sow colostrum quality, colostrum intake, piglet serum immunoglobulins, and pig growth. We took individual fecal samples from pigs in the weaning and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In this study, 52 strains belonging to nine species were identified: Lactobacillus animalis, Lactobacillus salivarius, Lactobacillus reuteri, Lactobacillus johnsonii, Lactobacillus crispatus, Enterococcus Montessori, Enterococcus sakazakii, Pseudostaphylococcus, Enterococcus hirae, and Enterococcus faecalis. These results were in line with previous studies that suggested that LAB strains are prevalent in pigs (König et al, 2021;Zhong et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, 52 strains belonging to nine species were identified: Lactobacillus animalis, Lactobacillus salivarius, Lactobacillus reuteri, Lactobacillus johnsonii, Lactobacillus crispatus, Enterococcus Montessori, Enterococcus sakazakii, Pseudostaphylococcus, Enterococcus hirae, and Enterococcus faecalis. These results were in line with previous studies that suggested that LAB strains are prevalent in pigs (König et al, 2021;Zhong et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The swabs were placed into cryotubes that were placed in a cool box, moved to a –18°C freezer within an hour and further to a –80°C freezer on arrival at the laboratory. Colostrum samples were milked within 6 hours from birth of the first piglet into sterile 10-ml plastic tubes after disinfection of the udder as described in detail in [76]. From one sow the colostrum sample was not obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal Lactobacillaceae abundance was determined as described elsewhere [ 21 ]. Briefly, ten-fold dilutions of fecal samples were plated on blood liver (BL) agar (Nissui Pharmaceutical, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%